Gold nanoparticle/polymer nanocomposite for highly sensitive drug–DNA interaction. Issue 8 (6th March 2015) - Kuralay, F.; Erdem, A.
Abstract : We demonstrate a gold nanaparticle/polyvinylferrocenium (AuNP/PVF + ) coated platinum (Pt) electrode for sensing highly sensitive DNA–anticancer drug interactions. Abstract : The interaction of the anticancer drug mitomycin C (MC) and DNA immobilized on gold a nanoparticle/polyvinylferrocenium (AuNP/PVF + ) coated electrode is presented. This is the first attempt to prepare a biocompatible nanoparticle/redox polymer composite in a one-step and easy electropolymerization procedure and then use the coated electrode for MC–DNA interaction. The prepared electrode exhibits high sensitivity for the investigation of drug–DNA interaction.